Metabolic syndrome and risk of incident peripheral artery disease: the cardiovascular health study. - Garg, Parveen K; Biggs, Mary L; Carnethon, Mercedes; Ix, Joachim H; Criqui, Michael H; Britton, Kathryn A; Djoussé, Luc; Sutton-Tyrrell, Kim; Newman, Anne B; Cushman, Mary; Mukamal, Kenneth J (Hypertension, 2014)
Prior studies evaluating metabolic syndrome (MetS) and incident peripheral artery disease (PAD) have been limited by use of modified MetS criteria and restriction to clinical PAD end points. We investigated MetS and risk of developing a low ankle-brachial index (ABI) and clinical PAD in the Cardiovascular Health Study, a population-based cohort of adults aged ≥65 years. Participants with MetS met at least 3 of 5 Adult Treatment Panel III criteria. Baseline C-reactive protein-MetS or fibrinogen-MetS were defined as presence of 3 of 6 components, with elevated C-reactive protein (>3 mg/L) or fibrinogen (>341 mg/dL) as a sixth component. Incident low ABI, defined as ABI <0.9 and decline of ≥0.15, was assessed among a subset of 1899 individuals with 2 ABI measurements 6 years apart. Over a median follow-up of 13.7 years, 4632 individuals were followed up for clinical PAD, defined as revascularization or diagnosed claudication. Adult Treatment Panel III MetS was associated with both incident low ABI (risk ratio, 1.26; 95% confidence interval [CI], 1.00-1.58) and clinical PAD (hazard ratio, 1.47; 95% CI, 1.11-1.94). Incorporating C-reactive protein or fibrinogen into Adult Treatment Panel III criteria identified an additional 16% to 20% of individuals as having MetS, and both C-reactive protein-MetS and fibrinogen-MetS were associated with incident low ABI (risk ratio, 1.36; 95% CI, 1.07-1.72 and risk ratio, 1.43; 95% CI, 1.13-1.81, respectively) and clinical PAD (hazard ratio, 1.56; 95% CI, 1.17-2.08 and hazard ratio, 1.55; 95% CI, 1.17-2.07, respectively). Among Adult Treatment Panel III MetS criteria, risk of PAD was most strongly associated with hypertension.
Keywords: Aged; Ankle Brachial Index; C-Reactive Protein; Female; Fibrinogen; Follow-Up Studies; Humans; Incidence; Longitudinal Studies; Male; Metabolic Syndrome; Peripheral Arterial Disease; Prevalence; Risk Factors; Vasculitis